2016
DOI: 10.1007/s12649-016-9603-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of Pretreated Pig Bristles with Crude Keratinase of Bacillus cereus PCM 2849

Abstract: Purpose The aim of the study was to apply and optimize the process of bioconversion of pig bristle waste using keratinolytic enzymes of Bacillus cereus PCM 2849, and to evaluate the amino acid composition of the resultant hydrolysate. Methods Hydrolysis with concentrated culture fluid of B. cereus was applied for bioconversion of pig bristles, after thermo-chemical pretreatment with sulfite. The effect of substrate concentration, sulfite concentration during pretreatment and reaction temperature on the release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on Łaba et al, the most abundant amino acids found from the pig bristle or hair hydrolysates were leucine and cysteine. 14 Proline is also an amino acid found in the hair. 15 The trypsin-digested keratin hydrolysate sample (Supporting Information S1) also confirmed that the sample is peptides with molecular weight ranging from 800 to 2600 Da.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Łaba et al, the most abundant amino acids found from the pig bristle or hair hydrolysates were leucine and cysteine. 14 Proline is also an amino acid found in the hair. 15 The trypsin-digested keratin hydrolysate sample (Supporting Information S1) also confirmed that the sample is peptides with molecular weight ranging from 800 to 2600 Da.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine (C), glycine (G), proline (P), isoleucine (I), or leucine (L) were identified. Based on Łaba et al, the most abundant amino acids found from the pig bristle or hair hydrolysates were leucine and cysteine . Proline is also an amino acid found in the hair .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Proteolytic bacilli, which belong to the most frequently characterized keratinolytic bacteria, typically produce a number of activity bands, e.g. 7 in the case of B. subtilis 1271 (Mazotto et al 2011 ) or 7 bands in cultures of B. cereus PCM 2849 (Łaba et al 2017 ), both grown in feather-containing media. In contrast, keratinolytic cocci produced fewer extracellular proteases, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments were described in individual studies, e.g. thermo‐chemical treatment (121°C, 20 min, 1 g bristle per 100 cm 3 sodium sulfite solution) (Łaba et al., 2016 ), or washing and degreasing with a methanol‐chloroform solution (Laba and Rodziewicz, 2014 ), among others. The main purpose of these treatments is the extraction of pure keratin and its subsequent conversion into smaller protein molecules of higher nutritional or industrial value through enzymatic, chemical or microbial based techniques.…”
Section: Assessmentmentioning
confidence: 99%